Variability in induction of defense response in Bengal gram against Trichoderma species - SUBHENDU JASH, SITANSU PAN* (Indian Phytopathology, 2010)
Ten isolates of Trichoderma spp., collected from diverse agro-ecological habitat of West Bengal, was evaluated against M. phaseolina to test the in vitro variability in antagonistic potential and also the ability to induce resistance in Bengal gram plant following Trichoderma treatment. T6 isolate grew rapidly and attained the S1 stage only on 4 days of incubation followed by T3, T4 while T2 isolate of T. harzianum was the least effective against the pathogen. The T9 isolates of T. roseum caused highest inhibition (47.41%) of mycelial growth followed by T7 (44.44%), T1 (39.63%) against M. phaseolina. Very low volatile substances released by T10 isolate of T. roseum also inhibiting only 19.26% mycelial growth. On the contrary, T6 and T10 isolates of Trichoderma also showed highest mycelial growth inhibition against the pathogen through production of nonvolatile antibiotic at 10% concentration. In the pre-inoculated plant there was an increase in activity of all the defense related enzymes tested as compared to control. T9 isolate of T. roseum induced highest PAL (4.4U) and ïƒ¢-1, 3 glucanase activity (272.4U) followed by T1 isolate of T. viride (4.2U) and T10 of T. roseum (263.6U), respectively. Very low ïƒ¢-1, 3 glucanase activity (10.88%) was found in inoculation with T7 isolate. Highest activity of peroxidase was noticed in the plant inoculated with T1 isolate (174.28U) followed by T9 (164.28U). Very low activity was found when the plant was inoculated with T8 isolate. Pretreatment of the roots of Bengal gram plants with different isolates of Trichoderma spp. was shown to systemically induce different defense related enzymes and the amount varies with the isolates irrespective of species and geographical habitat.